The prime choice of students of higher educational establishments from various regions of Ukraine concerning the types of physical activity (sports) (Pedagogy of Higher and Secondary Education, 2015)
Hloba T. A. The prime choice of students of higher educational establishments from various regions of Ukraine concerning the types of physical activity (sports).The prime choice of students of higher educational establishments from various regions of Ukraine concerning the types of physical activity (sports) is considered. The results of thequestionnaire survey of 290 university students from various regions of Ukraine are used in the research. The publications of scientists from different countries are analyzed concerning different types of students’ physical activity. Based on analysis of the literature and the conducted survey the ratio of students’ preference for types of physical activity (sports) is clarified. The urgency of theproblem as well as its viability has been proved.
Keywords: physical education; physical activity; student; training; table tennis